Primary leiomyosarcoma of the vulva – a rare occurrence - Rathore, Ruchi; Singh, Anju; Bhatla, Neerja; Mathur, Sandeep (Polish Journal of Pathology, 2023)
Vulval tumours are rare, representing merely 4% of all gynaecological neoplasms. 98% of vulvar lesions are benign, and only 2% are malignant. Of all vulvar malignancies, while squamous cell carcinoma is the most common malignancy, leiomyosarcomas of the vulva are extremely rare. Usually these tumours have nonspecific clinical manifestations, often leading to misdiagnoses of Bartholin cysts or abscesses. We describe a case of a 47-year-old woman who presented with a nonspecific painless swelling in the left vulva for 2 months which was diagnosed as leiomyosarcoma of the vulva on biopsy as well as resection.